Database Analysis of Long-Term Settlement Behavior of Pile Foundations in Shanghai Soft Coastal Clays - Qibiao Wang; Jie Li; Tao Fang; Shaohua Yu (Buildings)
A database of 195 field records of long-term settlement of high-rise buildings in Shanghai soft coastal clays is presented. The collected field records are divided into two categories based on pile type, i.e., bored pile and precast pile. Based on the settlement recorders collected, the long-term settlement behavior and settlement duration of the pile foundations in soft coastal clays are investigated. The statistical results show that the pile foundation in Shanghai soft coastal clays can be divided into three kinds of site conditions by considering the pile length and variation of long-term deformation behavior. Prediction models based on the power function are proposed to calculate the normalized final settlement for both bored pile and precast pile foundations. Based on the statistical results, the average normalized final settlement (settlement per floor), average settlement ratio (final settlement to the settlement when the superstructure is completed), and average settlement duration in the three site conditions for both bored pile and precast pile foundations are given. Additionally, an exponential settlement prediction model that can accurately forecast the entire settlement and post-construction settlement characteristics of buildings in Shanghai’s soft soil area is proposed. These statistical results can be referred to the preliminary foundation design works, which contribute to the quick evaluation of the possible settlement range, settlement ratio, and settlement duration of the proposed building constructed in the soft coastal clay area in Shanghai.